Staged Competition as a Driver of Construction Innovation. (2017) - Jensen, Christopher A.
Abstract: Globally building operation contributes 30-40% of the primary energy demand in most developed economies. At the same time the construction industry is repeatedly found to have lower rates of adoption of innovation than other industries, despite being described as "a lively source of new ideas". A general conclusion is that the rate of innovation lags behind most other sectors. A new mechanism for innovation generation, diffusion and adoption is required. The automotive industry provides a benchmark for innovation, and has a distinct advantage with regards to generation, implementation and adoption of innovation. Automotive 'staged competitions' (e.g. motorsport), occur within the industry between manufacturers, and rely heavily on the involvement of suppliers within the industry. Such competition provides an excellent platform for marketing, testing, and development of innovation within and beyond the parent industry. Although rare and fleeting, construction competitions already exist in the construction industry. However they are not as advanced as motorsport is for the purposes of generating, diffusing or adopting innovations. This case study research considers three unique existing construction competitions, and shows how each example can contribute to the increase in innovation in the construction industry. The research shows that none of the case study competitions are able to provide the required steps to progress radical innovation from generation to adoption, and are thus failing as a new innovation mechanism for the construction industry. Further discussion of how these competitions can be optimized to drive innovation within the construction industry is provided with the ultimate aim to reduce resource use and reduce greenhouse gas emissions.